ANALISIS PATHLOSS SINYAL LTE DENGAN MODEL COST 231-HATA DI KOTA PADANG - Ferry Hidayat; Delsina Faiza (Universitas Negeri Padang, 2019)
This research was conducted on the basis of the weakness of the received signal by service users (MS) caused by certain factors such as the geographical structure of a city, many buildings so that the path loss (Path Loss) resulted in data connection failure or call failure. This study serves to determine the comparison of Pathloss values in the Medium-Sized City and Large City Regions in Padang city with a 231-Hata cost propagation model. The measurement method used is the drive test using the Network cell Info LTE application and then analyzed with a model cost 231-Hata, the results of measurements with the RSRP standard research were carried out in the morning and evening for five days. The results showed: In Air Tawar BTS (Large City) by measurement and calculation of the Cost 231 Hata model, compared to the RSRP PT.XL Axiata Padang standard, the signal quality is medium category. While the Lubuk Buaya (Medium-Sized City) BTS is measured, and in the calculation of the Cost 231 Hata model. Compared to the RSRP PT.XL Axiata Padang standard, the signal quality is in Medium category. From the results of measurements and calculations there are differences in pathloss values that are not too significant. This is due to several factors such as building height, road width and geographical structure of the area.Keywords: RSRP, Pathloss, Drive Test, Cost 231 Hata,4G LTE